Feeding decisions for the newly weaned pigs in East Africa are weight dependent - Carter, N.; Dewey, Catherine E.; Grace, Delia; Lange, K. de (International Livestock Research Institute, 2015)
Introduction: Smallholder pig farmers in east Africa typically wean pigs at 6 to 8 weeks. Farmers report that commercially prepared pig diets are too expensive and therefore typically feed forage and food waste. This results in low average daily gain (ADG), especially for the newly weaned pig. The objective was to describe the weaning weights of local and crossbred Ugandan pigs purchased from smallholder farmers and to compare the growth rate of the pigs fed forage- or silage-based or commercial diets by their starting weights. Materials and Methods: Littermate local (n = 45) and crossbred (n = 45) Ugandan pigs were purchased from 14 smallholder farmers and individually weighed at 9 weeks of age. Pigs were randomly assigned to forage- or silage-based or commercial diets, housed in pens of 3 pigs and weighed every 3 weeks. Pigs on each diet were categorized into the lightest, middle, or heaviest tertile. Pig-level ADG was compared within diet and across diet by weight tertile multiple linear regression. Results: Average (SD) and range of body weight for 9-week-old pigs was 5.7 (1.6) and 2.8–10.2 kg for local and 8.0 (1.8) and 3.9 to 11.4 kg for crossbred pigs. From 9 to 20 weeks of age, 19 pigs gained less than 5 kg. All were fed either forage- or silage-based diets. Most pigs on these diets gained less than the smallest pigs fed commercial diet. For pigs fed forage-based, silage-based or commercial diets, the ADG of the lightest tertile of pigs was 18, -8 and 154 gm/d from 9–12 weeks and 115, 142 and 268 gm/d for 18–20 week old pigs fed forage-based, silage-based and commercial diets, respectively. Similarly, for these 3 diets, the ADG for the heaviest tertile of pigs was 32, 44, and 247 gm/d from 9–12 weeks, and 221, 332, and 319 gm/d for 18- to 20-week-old pigs. The ash levels ranged from 9–12, 12–20, and 9–11 % DM for forage-based, silage-based, and commercial diets. The high ash levels may in part explain the low ADG in the study. The highest ash levels were found in the first diets fed to the 9-week-old pigs because we included animal-grade dried fish dust rather than human-grade whole dried fish. The ash levels decreased when this change was made. Conclusion: At 9 weeks of age, there was a wide range of weaning weights for local and crossbred Ugandan pigs purchased from smallholder farms. Farmers should be encouraged to feed commercial diet until the pigs reach 11 kg of body weight. Older and heavier pigs grow well on less expensive forage-based and silage-based diets. ADG will likely be further improved when the ash content of diets can be reduced from both farmer made and commercial diets.